Perception of communities when managing exclosures as common pool resources in northwestern Ethiopia - Mekuria, Wolde; Getnet, Kindie; Yami, M.; Langan, Simon J.; Amare, D. (Wiley, 2021)
Understanding the different perceptions of the local community regarding the use and management of common pool resources, such as exclosures, could better support targeted interventions by government and development partners. Here, we report on a study conducted in the Gomit watershed, northwestern Ethiopia, using a survey and key informant interviews, to examine community perceptions on (a) the biophysical condition (i.e., challenge of land degradation and restoration), (b) the action situations (user's access to and control over resources and decision-making processes involved in taking actions in managing the exclosure), (c) actors' interactions (formal and informal institutions involved in the management of exclosures), and (d) perceived outcomes (benefits and tradeoffs of managing exclosures). Many people in the Gomit watershed recognize land degradation as a serious problem and believe that exclosures support restoration of degraded landscapes and improve ecosystem services. Informal institutions play a key role in managing exclosures by improving benefit sharing and mobilizing the local community for collective action. However, some community members have concerns about recent expansion of exclosures because of (a) limited short-term derived benefits, (b) reductions in fuelwood availability, (c) increased degradation of remaining communal grazing lands, and (d) poor participation of marginalized groups in decision making. Addressing such concerns through the promotion of short-term benefits of exclosures and increasing community participation in decision-making and benefit sharing is crucial. The study provides evidence to support government and development partners on the establishment and management of exclosures through identifying the benefits and drawbacks as perceived by different sectors of the community.